2001
DOI: 10.1093/jjco/hye051
|View full text |Cite
|
Sign up to set email alerts
|

A Nested Variant of Transitional Cell Carcinoma of the Urinary Bladder: a Case Report

Abstract: Nested variants of transitional cell carcinomas (TCC-NVs) are relatively rare neoplasms in the urinary bladder, but at least 25 cases have been described. This disease is characterized by the pathological finding of irregular nests and/or tubules of transitional carcinoma cells infiltrating the lamina propria without involvement of the mucosal layer. In our case, diagnosed by open biopsy, there were scattered tumor cells observed from the muscle layer to the subserosa, with a tendency toward increasing cellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 5 publications
0
15
1
2
Order By: Relevance
“…Tatsura and associates [12] stated that the nested variant of transitional cell carcinoma has the characteristics of a focus of nests of transitional epithelial cells which infiltrate the lamina propria with apparent involvement of bladder mucosa. They also suggested that immunohistochemical analysis may help in the diagnosis of nested variants of transitional cell carcinoma derived from epithelial cells and that diagnosis and treatment at an early stage should reduce the mortality of patients with nested variant of transitional cell carcinoma.…”
Section: Results/literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Tatsura and associates [12] stated that the nested variant of transitional cell carcinoma has the characteristics of a focus of nests of transitional epithelial cells which infiltrate the lamina propria with apparent involvement of bladder mucosa. They also suggested that immunohistochemical analysis may help in the diagnosis of nested variants of transitional cell carcinoma derived from epithelial cells and that diagnosis and treatment at an early stage should reduce the mortality of patients with nested variant of transitional cell carcinoma.…”
Section: Results/literature Reviewmentioning
confidence: 99%
“…They suggested that nested variant of urothelial carcinoma should be approached clinically as a high-grade disease with early cystectomy as an option for pT1 and pT2 tumours [2]. Dhall and associates [2] additionally stated the following that.Adjuvant chemotherapy and radiation therapy have not been shown by a number of authors to be significantly beneficial in their reported series [12, 20, 28]. …”
Section: Results/literature Reviewmentioning
confidence: 99%
“…Nuclei generally show little or no atypia, but invariably, the tumor contains foci of unequivocal cancer with cells exhibiting enlarged nucleoli and coarse nuclear chromatin. These malignant features are most apparent in the deeper aspects of the cancer [4][5][6][7][8][9]. 0046 Differential diagnosis.…”
Section: Nested Variantmentioning
confidence: 99%
“…El diagnóstico de CU variedad en nidos se fundamenta en la presencia de nidos irregulares, de tamaños y formas variables, desordenados y empaquetados, con escaso estroma entre ellos. Además, es clave en el diagnóstico y descarta cualquier entidad benigna, la infiltración de la muscular propia por nidos de células con mayor atipia nuclear 5,7,8,13,16,17 .…”
Section: Carcinoma Urotelial Variedad "En Nidos" Y/o "Tubular"unclassified
“…El diagnóstico de CU variedad en nidos se fundamenta en la presencia de nidos irregulares, de tamaños y formas variables, desordenados y empaquetados, con escaso estroma entre ellos. Además, es clave en el diagnóstico y descarta cualquier entidad benigna, la infiltración de la muscular propia por nidos de células con mayor atipia nuclear 5,7,8,13,16,17 .Las células tumorales de la variedad en nidos y/o tubular del CU muestran inmunohistoquími-camente positividad intensa y difusa con las citoqueratinas AE1/AE3 y CK7, y positividad sólo focal con CK20. A pesar de su apariencia histoló-gica benigna, la variedad en nidos del CU comparte algunas características con el CU convencional de alto grado.…”
unclassified